TRADISIONAL MAPPASORO FOR THE COMMUNITY IN BAJIMINASA VILLAGE RILAU ALE DISTRCT BULUKUMBA REGENCY - Nurfadilla Nurfadilla (Social Landscape Journal, 2022)
This study aims (1) to find out how the Mappasoro for the Bajiminasa village community (2) To determine the determinant factors influencing the Mappasoro for the Bajiminasa village community (3) To determine the efforts made to preserve the Mappasoro for the Bajiminasa village community. The type of research used is descriptive qualitative research. The data collection techniques in this study were by using the methods of observation, interviews, and documentation, then analyzed by qualitative descriptive techniques. The results of this study indicate that (1) the description of the Mappasoro of the Bugis in Bajiminasa Village, Rilau Ale District, Bulukumba Regency which is usually carried out by the Bajiminasa village community basically has three series of processions, namely: Mattihi Siesso (carrying a day), Mappicakka (Cleaning), and Marrekeng Henni (Counting the night) the three processions are considered to have good meaning by the community. This tradition is carried out as a form of love and remuneration to people who have helped in the management of the body and is considered a form of reward practice. (2) The determinant factor of the Mappasoro tradition seen from the economic factor has an important role because implementing this tradition requires a lot of money. So the size of this tradition is determined by the economic level of the community. In terms of education, it can be said that it is quite influential because people who have high education begin to think rationally so that things that are considered unreasonable are being abandoned. Whereas in the religious factor of the Mappasoro , from the beginning it was practiced by the community as a good deed which was taken in the teachings of Islam. (3) Efforts to preserve the Mappasoro in terms of the community are quite good because the people in Bajiminasa Village always participate in this tradition by taking an important role in it. However, the government itself has not been effective or maximal in efforts to preserve this tradition because there is still a lack of activities made by the government so that public interest is still very minimal in studying this tradition.